Determinant of the presentation of proxy of user assets report and its implication for the quality of financial statements (A case study at the Work Unit of KPPN Mataram) - Triko Slamet; Busaini .; Nur Fitriyah (STIE Perbanas Surabaya, 2016)
The purpose of this study is to determine the effect of human resource ability, information technology utilization, government internal control system, and organizational commit-ment towards the presentation of proxy of user assets report and the effect of the presenta-tion of proxy of user assets report on the quality of financial statement. The population consisted of the providers of proxy of user assets report and the providers of financial state-ments at the Work Unit of State Treasury Service Office (KPPN) Mataram as many as 726 people with a total sample of 88 people. This study uses four exogenous variables: human resource ability, information technology utilization, government internal control system, organizational commitment, and two endogenous variables: the presentation of proxy of user assets report and the quality of financial statements. Data collection technique used in this study is a survey by distributing questionnaires. Data analysis tool used is SmartPLS version 2.0 M3. The results show that the human resource ability and government internal control system have positive influence on the presentation of proxy of user assets report, information technology utilization and organizational commitment have no influence on the presentation of proxy of user assets report, and the presentation of proxy of user assets report has positive influence on the quality of financial statements.